Daratumumab provides a survival benefit in relapsed and refractory Multiple Myeloma, independent of baseline clinical characteristics: A meta‐analysis. Issue 4 (14th June 2021) - Cao, Congcong; Zhou, Xin; Ma, Qun
Abstract: Daratumumab was approved in patients with relapsed or refractory multiple myeloma (MM) who previously received proteasome inhibitors or immunomodulatory drugs. However, the efficacy and safety of the addition of daratumumab in subpopulations of patients with relapsed or refractory MM is still unknown. We systematically searched MEDLINE, EMBASE, and Cochrane for randomized controlled trials (inception to September 2020). All phase 3 randomized controlled trials (RCTs) which were conducted in patients with relapsed or refractory MM and compared the efficacy or safety with the addition of daratumumab versus control were adopted. Three studies including 1497 patients met our criteria. The addition of daratumumab increased the rates of overall response (RR 1.21, 95% CI 1.15–1.28, p  < .001), complete response or better (RR 2.43, 95% CI 2.00–2.96, p  < .001), very good partial response or better (RR 1.63, 95% CI 1.48–1.80, p  < .001) compared with those with control. No clear evidence of heterogeneity was found in comparisons of progression‐free survival obtained from subsets of studies grouped by the age of participant, ISS disease stage, type of measurable MM, the level of baseline renal function, cytogenetic profile. The results showed progression‐free survival benefit was consistent between the treatment groups regarding previous clinical therapy information. Patients receiving daratumumab had higher risks of lymphopenia and infusion‐related reactions of any grade and grade 3 or 4. In conclusions, this study provides a clear proof of beneficial effects of daratumumab‐based therapy in patients with relapsed or refractory MM with an acceptable safety profile. The progression‐free survival benefit was consistent regardless of patient's baseline characteristics or previous therapy agents. Abstract : Daratumumab‐based therapy provides beneficial effects in patients with relapsed or refractory MM with an acceptable safety profile. The progression‐free survival benefit was consistent regardless of patient's baseline characteristics or previous therapy agents